STEREOTYPING OF BEING MUSLIM IN AMERICA REFLECTED IN JOHAR‟S MY NAME IS KHAN (2010): A SOCIOLOGICAL APPROACH - HIDAYAH. ., AFIFAH NURUL (2010)
This research paper elaborates the stereotyping of being Muslim in America that is reflected in My Name is Khan movie, which are analyzed through sociological approach. The objectives of the research are to analyze the movie based on its structural elements and to analyze the movie by using Sociological approach. This research paper belongs to qualitative research. The sources of the data come from both primary data source, which is My Name is Khan movie and secondary data sources, which are the author's biography, essay, comment, historical information and other relevant information. The method to analyze the data is descriptive analysis. Having analyzing the movie, the writer comes to the conclusion as follows. First, based on the structural analysis of each element, it shows that all of the characters supported by the setting, plot and completed by perfect mise-en-scene, cinematography, sound and editing, finally form a good movie. Secondly, based on the sociological analysis, there is closed relation between the production of this movie and the social reality underlying it. The major factor that contributes to the production of this movie is the stereotyping of being Muslim in America after WTC attack. This movie also stresses on the sacrifice of a Muslim in America to prove that he is not a terrorist.